Asian Water Development Outlook 2025: the index of water security for Asia and the Pacific - Raman, V.; Ishii, S.; Kaur, S.; Guthrie, L.; Rodriguez, I. F.; Domingo, R.; Salazar, G.; Von Custodio, D.; Garcia, M. C.; Bautista, F. M.; Gonsalves, J. J. Jr.; Jordá, L. I.; et al. (Asian Development Bank, 2025)
The Asian Water Development Outlook (AWDO) assesses water security in Asia and the Pacific, evaluating 50 economies across five dimensions—rural, economic, urban, environmental, and water-related disaster security. This 2025 edition highlights significant progress: since 2013, 2.7 billion people have moved out of extreme water insecurity. Yet growing ecosystem stress and rising climate risks threaten these gains. With new analyses on investment needs, governance, and gender, the AWDO 2025 provides an evidence base for smarter, more inclusive policies and investments toward a water-secure, climate-resilient Asia and the Pacific.